Online validation of the 4 item Depressive Psychopathology Scale (DPS-4) in Peru - Lee-Diaz, Efrain (2024)
A diversity of scales are used as screening tools for depression in clinical settings and epidemiological research; however, many of them have a large number of items and are only validated in person. Objective: The aim of this study was the online validation of the 4-item short version of the Depressive Psychopathology Scale (DPS-4), taking as a reference standard the Depression Scale of the Center for Epidemiological Studies (CES-D). Materials and methods: A total of 256 participants answered a virtual survey, which included general questions about sociodemographic characteristics and background, the DPS-4 scale, and the CES-D. The structure of the DPS-4 was evaluated and its scores were contrasted with the diagnosis of depression defined by a CES-D score ≥24. Results: Taking the CES-D as the reference standard, the DPS-4 had an area under the ROC (receiver operating characteristic) curve of 0.9243 (95% confidence interval: 0.8899-0.9587) and the optimal cut-off point was 4 (Youden index: 0.7, sensitivity: 82.19% and specificity: 87.43%). Internal consistency was appropriate, with a McDonald's Omega coefficient of 0.8229. The item on anhedonia was the one that contributed the most to the measurement of the DPS-4. Conclusion: The online DPS-4 demonstrated adequate psychometric properties and proved to be valid for detecting depression, using the CES-D as a reference standard.